2018
DOI: 10.1038/s41598-018-20850-y
|View full text |Cite
|
Sign up to set email alerts
|

Attention Gates the Selective Encoding of Duration

Abstract: The abundance of temporal information in our environment calls for the effective selection and utilization of temporal information that is relevant for our behavior. Here we investigated whether visual attention gates the selective encoding of relevant duration information when multiple sources of duration information are present. We probed the encoding of duration by using a duration-adaptation paradigm. Participants adapted to two concurrently presented streams of stimuli with different durations, while dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…By using the logarithmic midpoint, we assure equal (perceptual) distance from the reference duration to the adaptation durations in the onset-offset matched and perceptually matched stimulus conditions. This procedure is similar to those used in earlier experiments, and allows us to measure the DAE as opposite shifts in perceived duration using the same range of test stimuli [11,14,15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By using the logarithmic midpoint, we assure equal (perceptual) distance from the reference duration to the adaptation durations in the onset-offset matched and perceptually matched stimulus conditions. This procedure is similar to those used in earlier experiments, and allows us to measure the DAE as opposite shifts in perceived duration using the same range of test stimuli [11,14,15].…”
Section: Methodsmentioning
confidence: 99%
“…Similar to these other stimulus features, support for the channel-based encoding of duration comes from studies demonstrating duration tuning in both behavioral and neuronal responses [1,10]. For example, several studies have shown that adaptation to duration leads to a duration after-effect (DAE) for subsequently presented durations [1,1115]. More specifically, these studies demonstrate that adaptation to a particular duration in one modality causes the perceived duration of subsequent durations in that same modality to shift away from the adapted duration.…”
Section: Introductionmentioning
confidence: 99%
“…We are interested in the potential to measure the (raw) ability of participants to bisect an interval and to also determine how well participants believed they performed in the task. Given that the percept of time is a fundamentally subjective estimate of the passage of physical time in the external world, which can be so easily disrupted by many factors both commonplace and otherwise (Ayhan et al, 2012;Brown & West, 1990;Cicchini & Morrone, 2009;Droit-Volet & Meck, 2007;Grommet et al, 2011;Maarseveen et al, 2018;Morgan et al, 2008), measuring metacognition in temporal tasks is an important extension to the current standards. We introduce this possibility here by asking the subjects to compare two consecutive time interval estimates and decide which they thought was the closer estimate to the actual midpoint of the test interval.…”
Section: Metacognition Of Timementioning
confidence: 99%